Association of collagen type I alpha 1 +1245G/T polymorphism and osteoporosis risk in post‐menopausal women: a meta‐analysis. (5th March 2017) - Wu, Jian; Yu, Meng; Zhou, Yixin
Abstract: Aim: To fully understand the association between collagen type I alpha 1 (COL1A1) +1245G/T polymorphism and osteoporosis risk in post‐menopausal women. Methods: We searched the electronic databases including PubMed, Embase and Cochrane library updated to January 2016, as well as printed articles. Studies were screened according to the predefined inclusion and exclusion criteria, and the included studies were further assessed by Clark scores system. Furthermore, the association between COL1A1 +1245G/T polymorphism and osteoporosis risk was assessed using odds ratios (ORs) and their 95% confidence intervals (95% CIs). Additionally, the meta‐analysis was carried out using Review Manger 5.1 software (Cochrane Collaboration, Oxford, UK) and Stata 11.0 software (StataCorp, College Station, TX, USA). Results: A total of five studies, which contained 1557 subjects (including 458 osteoporosis patients, 269 osteopenic patients and 830 normal controls), were included. Further, the included studies achieved Clark scores no less than 5, indicating a moderate or high quality. The pooled effect size indicated that there was a significant association between COL1A1 +1245G/T polymorphism and osteoporosis risk only under a co‐dominant model (GG vs . TT, OR = 2.45, 95% CI = 1.11–5.44, P  =   0.03). Moreover, there was no significant correlation between COL1A1 +1245G/T polymorphism and osteopenic risk under each model ( P  >   0.05). Conclusion: There might be a certain relationship between GG genotype of COL1A1 +1245G/T polymorphism and osteoporosis risk in post‐menopausal women.